The implementation of statistical process control on the drafting and drawing checking processes in a design office and the consequent improvement of the processes - Theart, Albertus Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1986.